In-situ permeability of the shallow backfill at Laohutai coal mine - ZHANG Jian; LIU Shouqiang; GUO Liangliang; LIU Qin (矿业科学学报)
The inherent water conductivity and permeability characteristics of artificial porous filling materials in underground mining pose potential water hazard risks to underground working faces.This study attempts to investigate the in-situ water conductivity of shallow filling materials in the Laohutai Coal Mine.We conducted laboratory testing, numerical analysis, and a combined connectivity test using sodium chloride and atmospheric precipitation to explore the permeability of the filling materials under natural conditions.Results indicate that the shallow filling materials primarily consist of shale mixed with slag, fly ash, and river sand.These materials feature low strength, poor cohesion, and high brittleness, with rapid strength degradation upon water exposure.The estimated average permeability coefficient from tracer tests aligned closely with numerical analysis results.Based on the combined sodium chloride and atmospheric precipitation connectivity tests, the conductivity curves of the underground monitoring points resulted from the combined effects of material composition and rainfall.The timing of conductivity inflection points at 5 monitoring locations reflected variations in the groundwater circulation rate within the filling body.The composition and distribution of the filling materials significantly influence their permeability, with an average permeability coefficient of 5.8 m/h.This is consistent with the results of tracer tests and numerical analysis.